Complication and cost analysis of transbronchial lung cryobiopsy and awake video-assisted thoracic surgery in diagnosis of interstitial lung disease: Cryobiopsy in diagnosis of interstitial lung disease - Katgı, Nuran; Çimen, Pınar; Çırak, Ali Kadri; Şimşek, Tarık; Ceylan, Kenan Can; Samancılar, Özgür; Duman, Elif; Erer, Onur Fevzi; Tuksavul, Fatma Fevziye (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2022)
Aim and introduction: Diagnosis of Interstitial Lung Disease (ILD) is difficult and costly. The standard diagnostical approaches to ILD are bronchoalveolar lavage, transbronchial lung biopsy, transbronchial lung cryobiopsy (TBLC) and surgical lung biopsy (SLB). SLB is the gold standard for diagnosis of ILD. We conducted a retrospective study to point out that TBLC plays an important role in diagnosis of ILD and has fewer complications and lower cost than awake video-assisted thoracic surgery (AVATS).Material and methods: 132 patients who underwent TBLC and AVATS with a pre-diagnosis of ILD in our hospital between 2015 and 2020 were evaluated retrospectively. Diagnosis rates, complications and costs were recorded.             Cryobiopsy in diagnosis of interstitial lung disease Results: There were no non-diagnostic materials in 44 patients in AVATS arm.  Prolonged air leak was observed in 11(25.0%) of the patients, and six of them (13.6%) were discharged with Heimlich Valve (HV). Median length of stay in the hospital was 8 days, while average patient cost was $515.9 (415.2-2662.9) in the AVATS arm.Non-diagnostic material was obtained from 6 (6.8%) of 88 patients in TBLC arm. Six of them (6.8%) had pneumothorax, only one of them required a chest tube. No patient was discharged with HV (p=0.001).  Median cost for each patient with a median hospital stay of  2.0 (1.0-21.0) (p